Gender Differences in Absolute and Relative Values of Hand Dynamometer Test with 9 and 10-Year Old Children From the Skopje Region in R.N. Macedonia - Abdulla Elezi; Gresa Elezi; Seryozha Gontarev; Georgi Georgiev (OVS LLC, 2021)
Background. Handgrip strength test is applied both to adults and children to indicate muscular fitness as well as the nutritional and health status. It differs in adults and adolescents depending on the gender. However, it is not clear whether a difference exists also in children at 9 to 10 years of age, and what are the factors that influence it. The goal of the research was to determine the absolute and relative values of the hand dynamometer test with healthy Macedonian boys and girls aged 9 and 10 from the Skopje region as well as to determine the factors that affect the handgrip strength at that age. Materials and methods. The research was conducted on a sample of 775 children (boys n = 386; girls n = 389), whereby the following characteristics were measured: handgrip strength, weight, height, body fat percentage, muscle mass percentage and the body mass index (BMI) was calculated. The maximum handgrip strength was measured with a digital Takei TKK 5101 dynamometer.  Results. The research found that there are statistically significant differences in the absolute values obtained in the hand dynamometer test between healthy boys and girls in Macedonia at 9 and 10 years of age. On the basis of the results obtained from the research, one can conclude that the results of the hand dynamometer test are affected by age, gender and body composition.  Conclusion. Based on the increasing predominance of children's obesity, the present study can provide clinicians and researchers with an insight how body composition influences muscular fitness, and can serve policy-makers to develop gender-specific strategies about body-weight management and promotion of muscular performance among children and adolescents.